Fluorescence-based immunosensor using three-dimensional CNT network structure for sensitive and reproducible detection of oral squamous cell carcinoma biomarker - Song, Chung Kil (2020)
A hierarchical three-dimensional network of carbon nanotubes on Si pillar substrate (3DN-CNTs) was developed for the accurate detection of oral squamous cell carcinoma (OSCC) in clinical saliva samples. The 3DN-CNTs were uniformly coated with a layer of aluminum oxides to enhance structural stability during biomarker detection. Cytokeratin-19 antigen (Cyfra 21-1) was utilized as a model biomarker of OSCC for fluorescence-based immunosensor using 3DN-CNTs (3DN-CNTs sensor). The 3DN-CNTs sensor enhances the sensitivity of Cyfra 21-1 detection by increasing the density of immobilized antibody through high surface area of 3DN-CNTs and enhancing the accessibility of biomolecules through the ordered pathway of hierarchical structure. The reliable detection limit for sensing of Cyfra 21-1 was estimated as in the level of 0.5 ng/mL and the quantitative estimation of Cyfra 21-1 was analyzed by 4-parameter logistic (4-PL) model for curve-fitting analysis. Clinical applicability of 3DN-CNTs sensor was evaluated through correlation with the commercially available electrochemiluminescence (ECL) detection system in the hospital. The assay results of the two systems for clinical saliva samples showed a good linear correlation. The 3DN-CNTs sensor offers great potential for accurate diagnosis of OSCC using Cyfra 21-1 biomarker in clinical fluids.